Is the persistent gender gap in income and wages due to unequal family responsibilities? - Nikolay Angelov; Per-Olov Johansson; Erica Lindahl (Institute for the Study of Labor (IZA), 2013)
We compare the income and wage trajectories of women in relation to their male partners before and after parenthood. Focusing on the within-couple gap allows us to control for both observed and unobserved attributes of the spouse and to estimate both short- and long-term effects of entering parenthood. Our main finding is that 15 years after the first child was born, the male-female gender gaps in income and wages have increased with 35 and 10 percentage points, respectively. In line with a collective labor supply model, the magnitude of these effects depends on relative incomes or wages within the family.
Keywords: J21; D13; C21; 330; gender gap; quantile regression; income; wages